SEXISM IN SOME OFFICIAL DOCUMENTS IN NIGERIA: IMPLICATIONS FOR GENDER EQUITY (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
The present study examines the lexical and grammatical forms of sexism in some official documents such as the national dailies, legal reports and the Nigeria constitution with a view to highlighting alternative usages that would create awareness for gender sensitivity in language use especially in Nigeria where such awareness is at its embryonic stage. Social constructivism and cohesion were adopted as the theoretical frameworks for the study in order to argue that gender category is a social construction and textual representations are the most efficient ways of sustaining such gender constructions using linguistic features that have become commonsense discourse markers. A qualitative method of data collection was employed; the focus being to identify the linguistic features, especially reference items that track certain antecedents representing important social/political positions in Nigeria, in order to determine whether they are sexist and discriminatory against any of the genders, especially the female. It was discovered that the three categories of Nigerian official documents studied are replete with sexist words and expressions that predominantly relegate the female gender to the background as non-contributors in the ideology-making process in Nigeria. Generic he/man and androcentric expressions observed in the documents studied seem to make women invisible in textual representation in Nigerian national dailies and the constitution. Moreso, the male-as-norm system of address used for both genders in legal reports studied undermines the robust representation of the female gender in the legal profession where a number of women had attained the highest echelon of office. The study recommends the use of epicene and gender-neutral terminologies to promote gender equity.
Keywords: EpiceneExpressions,Sexism,OfficialDocuments,GenderEquity